Determinants of Consumer Behavior Transformation from Traditional to Online Shopping: A Case Study of Central Java Community, Indonesia - Joko Suhariyanto; Farid A Rizky; Elvira Rahmaniar Rahmi (IAIN Syekh Nurjati Cirebon, 2025)
Technological advancements and the transition from traditional to online shopping have had a significant impact on consumer behavior. The availability of various online marketplace platforms has changed shopping habits, modified purchasing trends, and shaped overall consumption decisions. This study attempts to examine the influence of income, Islamic financial literacy, and social media on consumer behavior among individuals in Central Java, Indonesia. This study used a quantitative method. Data were collected through questionnaires from the Central Java population. A research sample comprising 458 respondents was obtained using simple random sampling. The independent variables include income, Islamic financial literacy, and social media, while the dependent variable is consumer behavior. Data were analyzed using SmartPLS software, involving a structural model (inner model) and a measurement model (outer model). This study revealed that Islamic financial literacy and social media have a significant impact on consumer behavior, while income does not show a significant effect. The coefficient of determination (Adjusted R Square) was 0.702 (70%), which indicates that income, Islamic financial literacy, and social media collectively influence 70% of consumer behavior with the remaining 30% attributable to unexplored factors. The transformation of the digital economy has brought multidimensional impacts on consumption behavior, from psychological to economic aspects. Thus, understanding these changes is important for academics, business practitioners, and policymakers in designing adaptive strategies for the digital ecosystem.